2021
DOI: 10.18805/ijar.b-1389
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Canine Distemper Virus in Different Diagnosis Materials of Dogs using Molecular and Pathological Methods, Northeastern Turkey

Abstract: Background: Canine distemper virus (CDV) is highly contagious disease that affects dogs despite several control measures. This study was aimed at investigating the presence of CDV nucleic acid in different clinical and tissue materials, from naturally infected dogs, by reverse transcriptase-polymerase chain reaction (RT-PCR) and to molecularly characterize distemper strains according to the partial Nucleoprotein (NP) gene sequence. Furthermore, tissue samples under went histopathological examination for distem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In this regard, the researchers suggest that the infection of young animals may be related to the virus-specific receptors in the immune system. In other words, the distemper virus receptors, such as signaling lymphocyte activation molecule (SLAM) in young dogs are far more than those in old dogs, leading to their high infection (Tatsuo et al, 2001;Yilmaz et al, 2022). In agreement with our study, Jóžwik & Frymus (2002) showed that 72% of dogs tested for distemper virus were younger than 1 year.…”
Section: Within Group Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…In this regard, the researchers suggest that the infection of young animals may be related to the virus-specific receptors in the immune system. In other words, the distemper virus receptors, such as signaling lymphocyte activation molecule (SLAM) in young dogs are far more than those in old dogs, leading to their high infection (Tatsuo et al, 2001;Yilmaz et al, 2022). In agreement with our study, Jóžwik & Frymus (2002) showed that 72% of dogs tested for distemper virus were younger than 1 year.…”
Section: Within Group Analysessupporting
confidence: 88%
“…Notably, inhibitors sometimes reduce the sensitivity of the quick test or even lead to false negative effects (Wilkes et al, 2014). In the study of Yilmaz et al (2022), the contamination of different dog samples was investigated using the RT-PCR method, and viral nucleic acid was detected at higher rates in the nasal swabs compared to the other samples. In their study, the samples were taken from dogs under 1 year old, and CDV was detected mainly in the respiratory secretion samples, consistent with our results.…”
Section: Between Groups Analysesmentioning
confidence: 99%
“…There are a number of studies on the molecular characterization of CDV in Türkiye. The first detected field CDVs have been found to belong to the European strains (Ozkul et al, 2004;O guzo glu et al, 2018;Yılmaz et al, 2022). In phylogenetic analysis, based on the H gene sequences, the Turkish sequences have appeared in a branch close to the Italian lineage, including wild CDV strains under the Arctic CDV lineage (Koç et al, 2021).…”
Section: Discussionmentioning
confidence: 99%